Determination of the İncidence and Types of Tooth Development Anomalies Using Cone Beam Computed Tomography - Özdemir, Adem; Ocak, Mevlüt Sinan (Ataturk Universitesi, 2025)
Objective: The aim of this retrospective study is to evaluate the presence of dental anomalies and the prevalence of anomaly types by examining cone beam computed tomography (CBCT) images obtained from patients presenting to the Faculty of Dentistry at Fırat University. Methods: CBCT images of 1180 patients referred to the Department of Oral, Dental, and Maxillofacial Radiology were utilized. Images of patients with intact teeth, devoid of prosthetic or endodontic treatments, lacking periapical lesions, and with completed root development were included. Basic descriptive statistics such as frequency analysis were employed for data analysis, while comparisons were made using the chi-square test and Fisher’s exact test. Results: Anomalies were detected in 125 out of 1180 patients (80 females, 45 males), totaling 176 anomalous teeth. The prevalence of dental anomalies was determined to be 10.6%. Distribution by gender revealed 12% in females and 8.72% in males. Through radiographic examination, the most commonly identified anomalies were taurodontism (4.1%), radix molaris (3.3%), dilaceration (3%), dens invaginatus (0.17%), and fusion (0.08%). No cases of gemination were encountered. Conclusion: Dentists should possess adequate knowledge regarding the prevalence of dental anomalies and their types, especially during root canal treatments. Misdiagnosis and improper treatment of a tooth with a planned root canal therapy due to dental anomalies can lead to treatment failure. The presence of dental anomalies can be successfully detected using CBCT, aiding in the assessment of root and canal structures of teeth. © 2025, Ataturk Universitesi. All rights reserved.
Diş Gelişim Bozukluklarının Görülme Sıklığının ve Tiplerinin Konik Işınlı Bilgisayarlı Tomografi Kullanarak Belirlenmesi
Keywords: CBCT; Dental Anomaly; Endodontics